Pengaruh Women’s March Terhadap Kebijakan Publik Di Indonesia Dan Amerika Serikat - Anggoro, Catur Wisnu; Rifai, Maulana; Marsingga, Prilla (Jurnal Ilmiah Wahana Pendidikan, 2025)
This research compares the impact of the Women's March in the United States and Indonesia on public policy in the political dimension. A qualitative approach is used to analyze its success in influencing policy. The Women's March was born as a response to issues of discrimination and gender inequality. In the US it focuses on the Trump administration, while in Indonesia it raises the issue of gender inequality and violence against women. The research method involved a review of literature in both countries. In the US, the Women's March had a major impact in increasing women's public awareness and political participation. In Indonesia, he played a role in ratifying the Migrant Worker Protection Law and the Sexual Violence Elimination Bill. Influencing policy changes and increasing public awareness of women's issues is proof of its success